The relieving effect of sun-dried protein tonic on sports fatigue - Li, S.; Zhang, B.; Ma, P. (Revista Brasileira de Medicina do Esporte, 2021)
Fatigue is a comprehensive process that involves many physiological and biochemical factors. It is a normal physiological reaction when human physical or mental activities reach a certain level. In recent years, it has been verified that free radicals are closely related to exercise-induced fatigue. Cardamine bursa purified selenoprotein has good oxygen-free radical scavenging ability and anti-lipid peroxide. It could protect mitochondria, liver, and red blood cells from peroxide injury. Therefore, it was speculated that the purification of selenoprotein Cardamine may play an active role in attenuating exercise-induced fatigue by scavenging free radicals. This study cleared the selenite protein Capsella bursa (SPC) as a research object, and evaluated its structural characteristics in relieving exercise-induced fatigue. The selenoprotein index system for exercise-induced fatigue was constructed by combining two AHP methods, principal component analysis and factor analysis. Purity, subunit composition, amino acid composition and RCM content were evaluated. The corresponding RCM protein was preliminarily predicted. The results showed that SPCH could significantly prolong the swimming time (P <0.01), improve the lactate clearance capacity (P <0.01), increase the glycogen content of the liver (P <0.01), and reduce the level of the BUN (P <0.05). SPCH has a good effect in relieving exercise-induced fatigue in mice, so it can be considered for development as a nutritional supplement to alleviate exercise-induced fatigue.